Role of osteopontin in psoriasis: An immunohistochemical study - M Yousry Abdel-Mawla; Kamal Ahmed El-Kasheshy; Soheir Ghonemy; Walid Al Balat; Amira Ahmed Elsayed (Wolters Kluwer Medknow Publications, 2016)
Background: Osteopontin (OPN) has been postulated to have a role in several T-helper (Th) 1 and Th 17-mediated diseases including psoriasis (PS), through multiple mechanisms sharing in the onset and worsening of PS, OPN shares in induction of keratinocyte proliferation through inhibiting keratinocyte apoptosis, OPN acts as a proinflammatory agent that participates in the upregulation of Th cell lineages, among which are the Th 1 and Th 17 cells. Aims and Objectives: The aim of this study was to explore the possible role of OPN in the pathogenesis of PS. Materials and Methods: This case-control study was carried out on 18 patients of chronic plaque PS (mean age 37.61 ± 14.48) and a control group of 18 apparently healthy volunteers (mean age 41.11 ± 11.02 years). Severity of PS was assessed using the PS area and severity index score. Two skin biopsies were taken from psoriatic patients. The first was taken from the lesional skin and the other from a counter apparently healthy site. Results: Our results showed statistically significant differences in the expression of OPN, between lesional and nonlesional skin as well as between nonlesional skin and control group (P ≤ 0.001). In addition, there was a significant difference in the expression of OPN, between control and lesional group. Conclusions: OPN involvement in PS enlarges the list of cytokines able to stimulate the inflammatory response in this disease, anti-OPN antibodies, may eventually become a useful therapeutic approach in PS.